The Correlation Between Students’ Narrative Text Identification Ability and Their Narrative Text Writing Ability - Padila Dewi (International Conference on Education and Language (ICEL), 2014)
In doing the research the writer used quantitative method. The research was conducted by using r product moment. The population of this research was all of students’ of grade eight in second semester of SMPN 20 Bandar Lampung in 2013-2014 that consisted of 763 students. The writer took 30 students as sample. In determining the sample, the writer used cluster sampling technique because the students’ achievements are heterogeneous. In collecting the data the writer used essay test.  The data was analyzed by using r-Product moment.The data were collected through the tests were which  statiscallyanalysed. r- product moment was applied. The result indicated that p-value 1%: 0.463 and 5%: 0.361 and t-test value was 742. Therefore, the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. The writer concluded that there is the correlation between students’ narrative text identification ability and their narrative text writing ability.